The cultural and legal perspectives on wife battering in Malaysia - Che Soh @ Yusoff, Roslina (2009)
Wife battering has become one of the major problems across the world. It cuts across lines of races, religion, income and classes of people. It is also deeply embedded in all cultures, so much so that millions of women consider it as a way of life. This article seeks to examine the cultural and legal perspectives on wife battering in Malaysia. In relation to cultural perspective, it attempts to address the issue of cultural beliefs of the major races in Malaysia, i.e. the Chinese, Indians and Malays, on this matter particularly pertaining to the extent of the husband’s authority over the wife which is claimed to be one of the contributing factors of wife battering. In relation to this, special emphasis is made on the misconception of wife battering in Islam. Finally, the article discusses the applicable laws and the available remedies and presents to what degree these laws are adequate in controlling the problem of wife battering in Malaysia.